Not a “Get Out of Jail Free Card”: Comparing the Legal Supervision of Persons Found Not Criminally Responsible on Account of Mental Disorder and Convicted Offenders - Martin, Sandrine; Charette, Yanick; Leclerc, Chloé; Seto, Michael C.; Nicholls, Tonia L.; Crocker, Anne G. (Frontiers in Psychiatry, 2022)
Background: The public often perceives the insanity defense as a “get out of jail free card”. Conversely, several studies demonstrate the substantial control imposed upon these defendants. This study compares Review Boards decisions regarding people found not criminally responsible on account of mental disorder (NCRMD) to criminal courts decisions regarding convicted offenders for similar offenses in Canada. Method: Detention, using logistic regression, and duration under detention and supervision, using Cox regression, were compared between a cohort of 1,794 individuals found NCRMD in three Canadian provinces (Quebec, Ontario, and British Columbia) between 2000 and 2005 followed until 2008 from the National Trajectory Project and a national sample of 320,919 Canadians convicted of criminal offense from Statistics Canada’s Criminal Court Survey. Results: Individuals found NCRMD are 3.8 times (95% CI 3.4-4.3) more likely to be detained than convicted offenders as well as 4.8 times (95% CI 4.5-5.3) and 2‧9 times (95% CI 2.6-3.1) less likely to be released from detention and supervision respectively. One year after the verdict, 73% of the NCRMD accused were still under legal supervision and 42% were still in detention, whereas these proportions were respectively 41% and 1% for their convicted counterparts. Interaction effects show that sex, age, jurisdiction, number, and type of offense have a differential impact on decisions applied to NCRMD accused compared to convicted persons. Conclusion: Contrary to popular perceptions, the insanity defense is not a loophole. Differences as to factors influencing the trajectories of the two samples confirm that Review Boards are able to distance their practices from the criminal courts and can set aside, at least in part, the principles of proportionality and punitiveness governing the traditional sentencing practices.